Anarchism and climate change activism - Mdladlamba, Thato (PINS-Psychology in Society, 2022)
Oscar Berglund & Daniel Schmidt (2020). Extinction Rebellion and Climate Change Activism. Breaking the law to change the world. Palgrave Macmillan. 108 pages. ISBN 978-3-030-48358-6 Extinction Rebellion (XR) is a popular and growing environmental and climate movement. Oscar Berglund and Daniel Schmidt critique the assumed link between XR and anarchism in this book. Although observers tend to associate XR’s lawbreaking protests with anarchists, the authors argue that this is often due to a lack of understanding of the idea of anarchism. The book, therefore, sets out to analyse and critique XR by focusing on how the discourses around XR, and its often lawbreaking practices, relate to the tradition of anarchism. The authors ask, why are observers of XR so quick to associate it with anarchism? Are they justified?